2023
DOI: 10.1515/med-2023-0720
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of low-risk birth care during the Covid-19 pandemic: A cohort study from a tertiary care center in Lithuania

Abstract: According to the World Health Organization, midwife-led care is the most appropriate and cost-effective type of perinatal care. As the Covid-19 pandemic with its drastic changes and challenges for the health systems and the medical staff made large adjustments to the healthcare delivery system, midwife-led care became an even more important supportive tool in maintaining unnecessary interventions. This retrospective cohort study aims to compare the outcomes of midwife-led care and team-led care in low-risk bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Woman-centered care, which emphasizes the unique individual needs, expectations, and aspirations of women, is often associated with midwife-led care [ 15 ]. However, while studies in Lithuania have investigated the effects of midwife-led care and obstetrician-led care on maternal and neonatal outcomes in low-risk deliveries [ 16 , 17 , 18 ], there remains a research gap regarding the holistic evaluation of physical and emotional patient-reported outcomes experienced by women during low-risk pregnancies, from their own perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…Woman-centered care, which emphasizes the unique individual needs, expectations, and aspirations of women, is often associated with midwife-led care [ 15 ]. However, while studies in Lithuania have investigated the effects of midwife-led care and obstetrician-led care on maternal and neonatal outcomes in low-risk deliveries [ 16 , 17 , 18 ], there remains a research gap regarding the holistic evaluation of physical and emotional patient-reported outcomes experienced by women during low-risk pregnancies, from their own perspectives.…”
Section: Introductionmentioning
confidence: 99%